Circulating microRNAs in plasma as early detection markers for breast cancer. Issue 7 (14th September 2012) - Cuk, Katarina; Zucknick, Manuela; Heil, Jörg; Madhavan, Dharanija; Schott, Sarah; Turchinovich, Andrey; Arlt, Dorit; Rath, Michelle; Sohn, Christof; Benner, Axel; Junkermann, Hans; Schneeweiss, Andreas; et al.
Abstract In recent years, circulating miRNAs have attracted a great deal of attention as promising novel markers for various diseases. Here, we investigated their potential to serve as minimally invasive, early detection markers for breast cancer in blood plasma. We profiled miRNAs extracted from the plasma of early stage breast cancer patients (taken at the time‐point of diagnosis) and healthy control individuals using TaqMan low‐density arrays (TLDA). Selected candidates identified in the initial screen were further validated in an extended study cohort of 207 individuals including 127 sporadic breast cancer cases and 80 healthy controls via RT‐qPCR. Four miRNAs (miR‐148b, miR‐376c, miR‐409‐3p and miR‐801) were shown to be significantly upregulated in the plasma of breast cancer patients. ROC curve analysis showed that the combination of only three miRNAs (miR‐148b, miR‐409‐3p and miR‐801) had an equal discriminatory power between breast cancer cases and healthy controls as all four miRNAs together (AUC = 0.69). In conclusion, the identified miRNAs might be of potential use in the development of a multimarker blood‐based test to complement and improve early detection of breast cancer. Such a multimarker blood test might for instance provide a prescreening tool, especially for younger women, to facilitate decisions about which individuals to recommend for further diagnostic tests.